Analisis Kepesertaan DPLK Secara Individu dan Karakteristiknya untuk Meningkatkan Penetrasi Dana Pensiun Pekerja Sektor Informal di Indonesia - Syarifudin Yunus; Farid Nabil Elsyarif (Pusat Riset dan Inovasi Nasional, 2025)
Research on the analysis of individual DPLK membership and its characteristics to increase the penetration of pension funds for workers in the informal sector was conducted using a descriptive qualitative approach with content analysis using questionnaires, interviews, and document studies. The research findings concluded that the individual characteristics of DPLK participants consist of: 1) belonging to the low-income group, 2) the highest contribution paid is Rp. 100,000 per month, 3) contributions may vary each month, 4) retirement age is determined based on financial goals, and 5) the motivation to join the DPLK is due to the lack of a pension program for old age or emergency funds. Currently, the composition of DPLK participants consists of: 20% individual participants (on their own initiative) and 80% corporate participants (enrolled by companies), while of the 560,000 individual DPLK participants, 70% come from the informal sector and 30% come from the formal sector. There are 86.4% of informal workers who have not prepared for retirement funds and 89.4% of informal workers who do not have voluntary pension programs. However, informal workers are interested in DPLK as a program for income continuity in their old age with the support of education and the availability of digital access. In terms of potential, if 25% of current informal workers participate in DPLK with a minimum contribution of IDR 50,000 per month, the potential accumulation of funds will reach IDR 132 trillion over the next 10 years as part of increasing pension fund penetration among informal sector workers.